EVALUATION OF THE USE OF AMLODIPIN IN HYPERTENSION PATIENTS IN THE HOSPITAL OF RSUD Drs. H. AMRI TAMBUNAN - Novidawati Boru Situmorang; Yayuk Anjani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Hypertension is a chronic disease that often becomes a problem in health. One of the treatment patterns for hypertension patients that is often received by patients at the RSUD Drs. H. Amri Tambunan is Amlodipine from the CCB (Calcium Channel Blocker) group. The goal of hypertension treatment is to prevent morbidity and mortality due to high blood pressure by reducing pressure to as low as possible so as not to interfere with kidney function, brain function and quality of life. Hypertension is a disease that occurs due to an increase in systolic and diastolic blood pressure values ??of more than 130/80 mmHg on two measurements with an interval of five minutes in a calm state. Hypertension is a condition in which a person experiences an increase in blood pressure above normal, namely systolic blood pressure 140 mmHg or diastolic blood pressure 90 mmHg. Every 10 kg weight loss of obese patients can reduce 5-20 mmHg Systolic Blood Pressure (TDS). The purpose of this community service activity is so that people who seek treatment at Drs. H. Amri Tambunan can monitor his health condition. With the evaluation of the drug amlodipine, participants become more aware of matters related to hypertension and can take advantage of herbal plants that grow around their homes to prevent or treat hypertension.